Analyzing Learning Obstacles in Differential Calculus: A Case Study of Pre-Service Mathematics Teachers in Indonesian Regional University - Ika Meika; Nenden Suciyati Sartika; Asep Sujana (Department of Mathematics Education Program IPI Garut, 2025)
Mahasiswa sering mengalami kesulitan dalam perkuliahan kalkulus diferensial. Tujuan penelitian ini adalah menganalisis karakteristik dari kesulitan belajar kalkulus diferensial pada mahasiswa calon guru matematika. Metode penelitian adalah kualitatif deskriptif dengan 39 mahasiswa dari dua Perguruan Tinggi Swasta di Banten, Indonesia. Data dikumpulkan melalui tes kesulitan belajar, wawancara, fokus grup diskusi (FGD) dan studi dokumen, dianalisis dengan teknik identifikasi, klarifikasi, reduksi, dan verifikasi secara naratif. Temuan penelitian menunjukkan 81% mahasiswa mengalami kesulitan pada aspek ontologis, 86% pada aspek didaktis, dan 73% pada aspek epistemologis. Solusi yang muncul dari wawancara dan FGD berupa kebutuhan mahasiswa terhadap buku sumber belajar yang interaktif dengan adanya elemen digital seperti video pembelajaran dan akses barcode. Pengembangan desain e-didaktis yang mengintegrasikan media digital ini tidak hanya membantu mengurangi hambatan belajar mahasiswa, tetapi juga berpotensi meningkatkan pemahaman konseptual sekaligus kemampuan aplikatif mereka dalam kalkulus diferensial. Learning obstacle ini menjadi pertimbangan bagi dosen dalam merancang desain e-didaktis pada kalkulus diferensial. Students often face challenges in differential calculus lectures. The purpose of this study was to analyze the characteristics of learning obstacles in differential calculus. The research employed a qualitative descriptive approach involving 39 students from two private universities in Banten, Indonesia. Data were collected through learning obstacle tests, interviews, focus group discussions (FGDs), and document studies, then analyzed using identification, clarification, reduction, and verification techniques in a narrative manner. The findings revealed that 81% of students experienced difficulties in the ontological aspect, 86% in the didactic aspect, and 73% in the epistemological aspect of differential calculus. Interviews and FGDs further confirmed the existence of these obstacles and explored potential solutions. One solution that emerged was the need for interactive learning resources incorporating digital elements such as instructional videos and barcode access. The implication of these findings indicates that developing an e-didactic design integrating digital media not only helps reduce students’ learning obstacles but also has the potential to enhance their conceptual understanding and applicative skills in differential calculus. Overall, these learning obstacles provide important considerations for lecturers in designing effective e-didactic materials for differential calculus courses.